2019
DOI: 10.1177/2041731419854586
|View full text |Cite
|
Sign up to set email alerts
|

In vivoimaging techniques for bone tissue engineering

Abstract: Bone is a dynamic tissue that constantly undergoes modeling and remodeling. Bone tissue engineering relying on the development of novel implant scaffolds for the treatment of pre-clinical bone defects has been extensively evaluated by histological techniques. The study of bone remodeling, that takes place over several weeks, is limited by the requirement of a large number of animals and time-consuming and labor-intensive procedures. X-ray-based imaging methods that can non-invasively detect the newly formed bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…In addition to ex vivo microCT evaluation, our group performed an in vivo assessment using microPET scans to identify active bone remodeling ongoing at the defect site. Several authors have demonstrated that this is a sensitive and valuable modality for evaluating bone regeneration following implantation of biomaterials 30,41,42 . Our results demonstrated a trend toward increased metabolic activity within the XG groups when compared to DBM.…”
Section: Discussionsupporting
confidence: 58%
“…In addition to ex vivo microCT evaluation, our group performed an in vivo assessment using microPET scans to identify active bone remodeling ongoing at the defect site. Several authors have demonstrated that this is a sensitive and valuable modality for evaluating bone regeneration following implantation of biomaterials 30,41,42 . Our results demonstrated a trend toward increased metabolic activity within the XG groups when compared to DBM.…”
Section: Discussionsupporting
confidence: 58%
“…defects smaller than this size can regenerate spontaneously, previous studies by our group have shown 5 mm to be critical [30]. Moreover a number of studies have chosen a 5 mm defect as a standard bilateral skull defect in the rat to minimize the animal numbers used and meet the 3R criteria (Reduction, Replacement, Refinement) [31,32]. Also, a defect of the cranium is a commonly used model to evaluate bone reconstruction due to the absent blood supply, lack of muscle tissue and poor bone repair [31].…”
Section: Discussionmentioning
confidence: 99%
“…As ions released from these glasses already exist in the body, problems related to toxicity and inflammatory reactions are avoided (Foroutan et al, 2015). However, silicate-based glasses have a poor solubility and typically they take several years to dissolve in a physiological environment (Fragogeorgi et al, 2019). Therefore, they cannot be used as temporary implants and their long-term effects in the body are still unknown.…”
Section: Introductionmentioning
confidence: 99%